1998
DOI: 10.1023/a:1018670129611
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Treatment of psychological problems of 59 children with a physical intersex condition is described. The group consisted of 18 female pseudohermaphrodites with congenital adrenal hyperplasia (CAH), 20 male pseudohermaphrodites and 2 true hermaphrodites born with ambiguous external genitalia assigned the female sex (ambiguous girls), 14 male pseudohermaphrodites born with completely female external genitalia and assigned the female sex (completely female group), and 5 male pseudohermaphrodites born with ambiguou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Presently, intersex children are still considered in formal diagnostic manuals for pediatricians and clinicians to have a "disorders of sexual development," and many clinics conduct surgical or hormonal treatments to "correct" these "problems" (e.g., Slijper & Drop, 1998), with others working to prevent the birth of intersex babies in the first place (New et al, 2001). Thus, intersex children continue to be seen through a lens of "atypicality as pathology" though there is a growing movement to change this perception (Dreger, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, intersex children are still considered in formal diagnostic manuals for pediatricians and clinicians to have a "disorders of sexual development," and many clinics conduct surgical or hormonal treatments to "correct" these "problems" (e.g., Slijper & Drop, 1998), with others working to prevent the birth of intersex babies in the first place (New et al, 2001). Thus, intersex children continue to be seen through a lens of "atypicality as pathology" though there is a growing movement to change this perception (Dreger, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Some number of children with ambiguous genitalia (one type of intersex condition) are raised as boys and some as girls, some are aware they were born intersex, some are not, yet within each group, some later identify as male, some as female, and some as something in between (e.g., Slijper & Drop, 1998). Although not a true experiment, this configuration of environments, perhaps in combination with the study of transgender children who, for example, are or are not allowed to "socially transition" to live as the "other" gender, could allow researchers to better separate the impact of gender socialization on gender outcomes.…”
Section: The Experiences Of Individuals With Gender-and Sex-diverse Imentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CAIS are always raised as girls, their gender role behavior and gender identity are female [2], their sexual orientation is heterosexual [3, 4, 5]. Children with partial androgen insensitivity (PAIS) usually present directly at birth because of ambiguous external genitalia.…”
Section: Introductionmentioning
confidence: 99%
“…Froukje [2] and Meyer-Bahlburg et al [3] concluded from a study of gender change from female to male in four adult 46,XX patients with congenital adrenal hyperplasia (CAH) that gender atypical self and body images are the most important factors in the development of crossgender identity.…”
Section: Introductionmentioning
confidence: 99%